Report of the 36th annual conference held in the Usher Hall, Edinburgh, October 5th - October 9th, 1936. - Labour Party (London : Labour Party, 1936)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Labour Party; Groot-Brittannië.